Globalisme dan Multi-Versalisme: Beberapa Catatan tentang Dinamika Sosial Budaya di Bali - I Ketut Ardhana (Jurnal Kajian Bali (Journal of Bali Studies), 2011)
AbstractGlobalism has variously impacted on the social, cultural, economic, legaland political life of the Balinese, which in turn has changed the structure ofBalinese society. Ultimately, this could also create conflicts or other socialproblems. Indeed, there are many regulations to anticipate and to dealwith such issues, but these have not been satisfactory due to weaknessesin implementation. This can be seen in the way issues on globalism affectideas of multi-versalism, which could in turn foster particular changestowards sustainable development in Balinese society.The majority of people who reside in the Bali Island are Balinese, whoare adherents of Hinduism. The Balinese have attempted to solve theproblems caused by globalization not only in the context of their dailylife, but also in the context of religion. It is important to note here thatthe religious issues are closely linked with the local issues, especiallythose dealing with their longstanding cultural. This essay will addressseveral issues: firstly, how globalism affects social, cultural, economic,and political aspects of Balinese life; secondly, how the Balinese anticipateor solve contemporary problems; and finally how the global and nationalissues have been tackled by the Balinese society through local wisdom.An analysis of these important issues is expected to offer a betterunderstanding of globalism in the context of Balinese local wisdom andthe ideas of multi-versalism.